ermA,ermC,tetM and tetK are essential for erythromycin and tetracycline resistance among MRSA strains isolated from a tertiary hospital in Malaysia - Lim, K.T.; Hanifah, Y.A.; Yusof, M.Y.M.; Thong, Kwai Lin (Medknow Publications, 2014)
The objective of this study was to determine the expression and transferability of tetracycline and erythromycin resistance among 188 MRSA strains from a Malaysian tertiary hospital. The minimum inhibitory concentrations (MICs) for oxacillin, erythromycin, tetracycline and ciprofl oxacin ranged from 4 to 512 μg/ml, 0.25 to 256 μg/ml, 0.5 to 256 μg/ml and 0.5 to 512 μg/ml, respectively. Tetracycline-resistant strains showed co-resistance towards ciprofl oxacin and erythromycin. There was a signifi cant increase (P<0.05) of high-level tetracycline (≥MIC 256 μg/ml) and erythromycin (≥MIC 128 μg/ml) resistant strains in between the years 2003 and 2008. All erythromycin-resistant strains harboured ermA or ermC gene and all tetracycline-resistant strains harboured tetM or tetK gene. The blaZ was detected in all MRSA strains, whereas ermA, tetM, ermC, tetK and msrA genes were detected in 157 (84%), 92 (49%), 40 (21%), 39 (21%) and 4 (2%) MRSA strains, respectively. The blaZ, tetM, ermC and tetK genes were plasmid-encoded, with ermC gene being easily transmissible. Tn5801-like transposon was present in 78 tetM-positive strains. ermA and tetM genes were the most prevalent erythromycin and tetracycline resistance determinants, respectively, in MRSA strains. The association of resistance genes with mobile genetic elements possibly enhances the spread of resistant traits in MRSA.